Pyronaridine-artesunate Efficacy and Safety in Uncomplicated Plasmodium falciparum Malaria in Areas of Artemisinin-resistant Falciparum in Viet Nam (2017–2018). (28th June 2019) - Quang Bui, Phuc; Hong Huynh, Quang; Thanh Tran, Duong; Thanh Le, Dong; Quang Nguyen, Thieu; Van Truong, Hanh; Khim, Nimol; Witkowski, Benoit; Cong Tran, Dai; Bustos, Maria Dorina; Ringwald, Pascal; Thi Ta, Tinh
Abstract: Background: Multidrug-resistant Plasmodium falciparum undermines the efficacy of currently deployed antimalarial therapies in southern Viet Nam. Methods: Between May 2017 and December 2018, this prospective, open-label, single-arm, observational clinical trial, conducted in Binh Phuoc, Dak Nong, Gia Lai, Khanh Hoa, and Ninh Thuan provinces, evaluated the safety and efficacy of oral pyronaridine-artesunate once daily for 3 consecutive days in adults and children with microscopically confirmed P. falciparum malaria. Patients were treated as inpatients for Days 0–3, with follow-up visits on Days 7, 14, 21, 28, 35, and 42. The primary outcome was the proportion of polymerase chain reaction (PCR)-adjusted adequate clinical and parasitological response (ACPR) at Day 42. Results: The cumulative incidence of PCR-adjusted ACPR at Day 42 was 96.1% (95% confidence interval [CI] 91.4–98.2; Kaplan–Meier). In the per-protocol analysis, the proportion of patients with Day 42 PCR-adjusted ACPR was 96.1% (147/153; 95% CI 91.7–98.5). The proportion of patients with parasitemia at Day 3 was 24.0% (40/167; 95% CI 17.7–31.2). The prevalences of the Kelch13 (C580Y) mutation were: in Binh Phuoc, 97.7% (43/44); in Dak Nong, 96.2% (25/26); in Gia Lai, 57.8% (37/64); in Khanh Hoa, 66.6% (6/9); and in Ninh Thuan, 3.6% (1/28). The majority of artemisinin-resistant isolates also had increased plasmepsin2 copy number (75.9%; 85/112). There was 1 isolate (Binh Phuoc) that had Kelch13 (C580Y) plus increased plasmepsin2 and Pfmdr1 copy numbers. Asymptomatic transient increases in alanine transaminase and aspartate transaminase were observed at Day 7, resolving by Day 28. Conclusions: Pyronaridine-artesunate can be used to diversify antimalarial therapy in areas of artemisinin-resistant P. falciparum in Viet Nam. Clinical Trials Registration: ACTRN12618001274268. Abstract : In areas of known artemisinin resistance in Viet Nam, pyronaridine-artesunate has utility in treating uncomplicated Plasmodium falciparum malaria.